MODELS AND METHODS OF IMPROVING THE EFFICIENCY OF WIRELESS ACCESS OF TELECOMMUNICATION SYSTEMS AND NETWORKS - Stelyuk, B. B.; Tkhorzhevskyi, D. O.; Khalipova, N. V. (Systems and Technologies, 2021)
The peculiarities of construction of complex information and telecommunication systems of special purpose are researched in the work, the general and special requirements to the applied telecommunication technologies are substantiated on the example of the automated territorially distributed system of the uniform regional operative and dispatching centers. To take into account certain properties of the generated authorization keys, a comprehensive model of authorization and authentication of wireless access is proposed for the security assessment of telecommunication systems and networks. The proposed territorial distribution systems of unified regional operational control centers for special purposes are based on the deployment of wireless telecommunication systems and must meet the basic requirements of users with high mobility. Consider the capabilities of these systems in terms of fulfilling special requirements for ensuring the security of national information resources, personal data, information with limited access and the security of communication protocols, etc. An analysis is carried out in the specification of IEEE 802.16 series standards on the use of various cryptographic protection mechanisms designed to provide various security services and security in wireless telecommunication networks, representing various attacks aimed at disrupting the operation of authentication and authorization protocols. The communication protocols used in the deployment and use of wireless telecommunication systems that provide an increased level of security, especially regarding the issues of unauthorized interception of transmitted data and unauthorized access to various telecommunication resources, and violations associated with false authentication of devices in relation to users of certain elements of telecommunication systems. Basic models of wireless telecommunication systems are proposed, which are deployed in accordance with the IEEE 802.16 specification and can be used to build various information systems for special purposes, including geographically distributed systems of unified regional operational control centers in Ukraine.